Evolution in the official Olympic wrestling regulation and its impact on the physical fitness profile and technical/tactical skills - José María López-Gullón; Alberto Martínez-Abellán (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract The Federation Internationale de Lutte Amateur (FILA), the lead agency responsible of the Olympic Wrestling since 1912, has carried out numerous modifications of the official wrestling rules. These changes have also promoted a very different wrestling style compared to the beginning of the twentieth century. This update has been mainly focused on establishing a strict weight class system as well as the reduction in the duration of combats and their respective periods or bouts. Furthermore, these rules changes have led to a better balance out in the physical characteristics between wrestlers, a tight control on the tournament programs and schedules, a decrease in the risk of injury or physical damage between counterparts, as well as an increase in the percentage of performance that depends on technical and psychological skills. In this review the authors aim to perform a chronological description of these rules changes as well as the consequences that these modifications have promoted on the Olympic Wrestling of the XXI century. Key words:  Freestyle; female wrestling; greco-roman; combat; tournament